Combination of Synchronous and Asynchronous Models in Online Learning - Intan Nuyulis Naeni Puspitasari (Program Pascasarjana Universitas Ibrahimy, 2021)
The implementation of an online learning system due to the Covid-19 pandemic has become a portrait of learning today and the future. Since March 2020 online learning implemented at the IAIN Kediri demands the readiness of lecturers and students to adapt to learning. The researcher as one of the lecturers who is directly involved in online learning has implemented a combination of synchronous and asynchronous learning settings through several learning media. This article is a self-study with a qualitative approach to the researcher's experience in carrying out online learning for one semester. The main question of this research is how do lecturers optimize the student learning experience in online learning using a combination of synchronous and asynchronous models?. A preliminary survey of students at the beginning of the semester and a reflection at the end of the semester researchers used as primary data sources to gain their insight into the online learning experience. Researchers found that this combination of synchronous and asynchronous models was proven to be more able to help students to be directly involved in learning activities and to feel a connection with their peers and lecturers. So that lecturers need to balance the flexibility provided by online space with the synchronous learning environment, according to the abilities and needs of students, as well as providing meaningful and quality learning spaces to achieve planned learning objectives.